A difference that matters: the aortic root anatomy of large animal models vs. humans - Strauss, Venessa; Appa, Harish; Human, Paul; Vogt, Ferdinand; Hadasha, Waled; Scherman, Jacques; Said-Hartley, Qonita; Schneeberger, Yvonne; Bergmeister, Helga; Conradi, Lenard; Podesser, Bruno K.; Zilla, Peter (Frontiers in Cardiovascular Medicine, 2025)
IntroductionThe development of transcatheter aortic valve devices critically depends on preclinical testing in large animal models, yet key anatomical differences between these models and humans remain insufficiently defined. This study evaluated the translational relevance of ovine and porcine models by comparing aortic root anatomy with that of healthy individuals and patients with aortic valve disease.MethodsSilicone root casts and ECG-gated computed tomography (CT) imaging were used to assess annular, sinus of Valsalva (SOV), and sinotubular junction (STJ) dimensions, as well as coronary ostial height and eccentricity. ResultsPigs and sheep exhibited significantly lower and more laterally displaced left coronary ostia compared to humans—features that may predispose to coronary obstruction during valve implantation. Body weight correlated with key root dimensions, but wide individual variability precludes its use for selecting individual animals. However, it remains a useful filter for defining cohorts from which suitable subjects can be selected using CT. Sheep demonstrated flatter sinuses and lower STJ heights than pigs and humans, further reducing coronary inflow clearance. In contrast, coronary heights in humans were consistent across valve pathologies, with sinus dimensions being the most variable feature.ConclusionValidation of ex vivo silicone casting against in vivo CT confirmed its suitability for scalable anatomical assessment while aligning with animal welfare principles. These findings support refinement of animal selection strategies and provide an anatomically grounded framework for preclinical evaluation of transcatheter valve technologies.